Research on a Unified Framework Based on Linear Frequency Modulation and Orthogonal Frequency-Division Multiplexing - Zhang, Tianhong; Xu, Limei; Qin, Kaiyu; Yan, Xiao (Journal of Computer Networks and Communications, 2019)
This paper proposes a unified system framework based on linear frequency modulation (LFM) and orthogonal frequency-division multiplexing (OFDM) as a solution for resource sharing, especially sharing space and hardware. The proposed OFDM-LFM framework can not only transmit data flow by OFDM but also make it possible to extract features from the signal by LFM. Further, the signal features are used to construct a pseudospectrum related to the target speed and distance, thereby estimating the speed and distance of the target. Unified means using signal features to estimate target speed and distance while ensuring data transmission including communication and remote control data information. Besides the traditional data transmission mode, the ability of estimating target speed and distance is an additional benefit. The proposed unified framework makes control of transmission easier and saves more hardware resources. The simulation results show that the proposed LFM-OFDM framework can not only transmit data information including communication and remote control data information, but also estimate the speed and distance of the target by its signal features.